The Process of Organizing the Increase in Financial Literacy in Higher Educational Institutions (European Journal of Economics, Finance and Business Development, 2024)
The life cycle of any person includes certain events that need to be financially prepared for. Japanese scientists at Nagoya University and Hiroshima University found a link between understanding the patterns of the financial system and stress. Experts say that people who understand finances are less prone to stress and anxiety. It doesn't matter if they are rich or not. The purpose of the article is to show the features and capabilities of the country's regional universities in solving the problem of increasing the financial literacy of young students.